Agglomeration and collection of fine secondary phases in flowing suspensions utilizing resonant ultrasonic fields - 217787 Tolt, Thomas Lester (Ann Arbor, MI : UMI, 1990)
Thesis (Doctor of Philosophy) - Case Western Reserve University, 1990